2014
DOI: 10.1152/japplphysiol.00204.2014
|View full text |Cite
|
Sign up to set email alerts
|

Range of motion, neuromechanical, and architectural adaptations to plantar flexor stretch training in humans

Abstract: Blazevich AJ, Cannavan D, Waugh CM, Miller SC, Thorlund JB, Aagaard P, Kay AD. Range of motion, neuromechanical, and architectural adaptations to plantar flexor stretch training in humans. 117: 452-462, 2014. First published June 19, 2014 doi:10.1152/japplphysiol.00204.2014.-The neuromuscular adaptations in response to muscle stretch training have not been clearly described. In the present study, changes in muscle (at fascicular and whole muscle levels) and tendon mechanics, muscle activity, and spinal motone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
134
4
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(156 citation statements)
references
References 53 publications
15
134
4
3
Order By: Relevance
“…The numerical values may indicate that muscle contributes to a greater extent in dancers (63% of maximal MTU elongation) compared to controls (53%); however, these differences did not reach statistical significance. Greater contribution from muscle would be in agreement with Abellaneda et al, where fascicles contributed 72% and tendon 28% at 30° dorsiflexion, and an intervention study which found increased muscle and fascicle strain and decreased tendon strain at a constant joint angle following stretching training . Taken together, these findings suggest that the capacity for muscle elongation plays an important role for ROM.…”
Section: Discussionsupporting
confidence: 88%
“…The numerical values may indicate that muscle contributes to a greater extent in dancers (63% of maximal MTU elongation) compared to controls (53%); however, these differences did not reach statistical significance. Greater contribution from muscle would be in agreement with Abellaneda et al, where fascicles contributed 72% and tendon 28% at 30° dorsiflexion, and an intervention study which found increased muscle and fascicle strain and decreased tendon strain at a constant joint angle following stretching training . Taken together, these findings suggest that the capacity for muscle elongation plays an important role for ROM.…”
Section: Discussionsupporting
confidence: 88%
“…The greater hip ROM reached in the passive tests after fatigue condition could be due to changes in the mechanical properties (i.e. muscle stiffness or viscoelastic deformation) (Magnusson et al, 1996), changes in stretch reflex activity (Blazevich et al, 2014) or greater subjective tolerance to passive stretch (Magnusson et al, 2001). Stretch tolerance can be defined as the ability of a participant to tolerate an increase in the discomfort of the stretching procedure at the terminal range of motion (Reid and McNair, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it becomes hard to consider sarcomerogenesis as a possible mechanism for increased performance following flexibility training. A recent investigation [31] reviewed six studies [26,28,[32][33][34][35] that evaluated the influence of static stretching training on isometric contractions. The authors observed that none of the included studies showed any improvement in performance after flexibility training using static stretching.…”
Section: The Influence Of Chronic Stretching On Muscle Flexibility Anmentioning
confidence: 99%